LEGAL ANALYSIS OF PRODUCTS, SERVICES AND SERVICE QUALITY IN INFLUENCING CUSTOMER SATISFACTION AT BANK SYARIAH MANDIRI IN JAYAPURA CITY - Pelupessy, Eddy (Penerbit Lafadz Jaya, 2025)
This research, entitled